Serviceability Assessment of Continuous Beams Strengthened by SMA Strands under Cyclic Loading - Fatemeh Azadpour; Ali Akbar Maghsoudi (Civil Engineering Journal, 2019)
Since the wide cracks or large deflections can have a significant effect on the appearance of concrete elements and may cause some uncommon behavior, therefore, serviceability of concrete structures requires investigation. The main objective of this paper is to study experimentally the serviceability of continuous reinforced concrete (RC) beams strengthened by Ni-Ti strands. In addition, some building code provisions were used to calculate crack width and deflection. The current study presents the experimental results to verify the accuracy of building codes’ provisions for continuous RC beams strengthened by SMA strands. Although a pattern of smaller width cracks was monitored for strengthened beams, more than 50% of the crack widths were recovered because of super elastic SMA strands. The performance of crack width provisions illustrates an overestimated crack width for SMA RC beams. Moreover, the predicted values for immediate deflections based on building codes provided a good agreement, although the effective reinforcement ratio (steel reinforcement and SMA strands) had a significant effect on immediate deflections of reinforced concrete beams strengthened by SMA strands under service loads.